PENGARUH PERGAULAN TEMAN SEBAYA DENGAN KECERDASAN EMOSI ANAK USIA 5-6 TAHUN DI TK CENDANA RUMBAI KECAMATAN RUMBAI PESISIR KOTA PEKANBARU - Ritonga, Ayu Satria; Chairilsyah, Daviq; Febrialismanto, Febrialismanto (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2019)
Abstract: This research aims to know the influence of peer association with Kecamatan Rumbai Pesisir Rumbai Kecamatan Rumbai Pesisir city Pekanbaru. The population in this research is the whole child in TK Cendana Rumbai Kecamatan Rumbai Pesisir town of Pekanbaru aged 5-6 years. Class B1-15 children and grade B2-15 children. Total children about 31 children. The method used is correlation using simple regression techniques. The data collection techniques used are observations. Data analysis techniques using scale trials and statistical method analysis with IBM SPSS Ver. 23 program. Based on the results of the hypothesis test, there is a positive and significant influence between peer association with emotional intelligence of children aged 5-6 years in Cendana Rumbai Kecamatan Rumbai Pesisir city Pekanbaru. To find out if there is an influence of peer association to emotional intelligence children aged 5-6 years at TK Cendana Rumbai Kecamatan Rumbai Pesisir city Pekanbaru. Can be seen from the correlation that indicates Thitung = 6,548 with the significance of 0.000. While this research is 2.024 it can be concluded there is a significant influence of peer association to the emotional intelligence of children aged 5-6 years in TK Cendana Rumbai Pesisir Pekanbaru.Key Words: Peer-To-Peer Intercourse, Emotional Intelligence